Audiovisual emotion perception develops differently from audiovisual phoneme perception during childhood. - Hisako W Yamamoto; Misako Kawahara; Akihiro Tanaka (PLoS ONE, 2020)
This study investigated the developmental paths in the use of audiovisual information for the perception of emotions and phonemes by Japanese speakers. Children aged 5 to 12 years and adults aged 30 to 39 years engaged in an emotion perception task in which speakers expressed their emotions through their faces and voices, and a phoneme perception task using phonemic information in speakers' lip movements and speech sounds. Results indicated that Japanese children's judgement of emotions by using auditory information increased with increasing age, whereas the use of audiovisual information for judging phonemes remained constant with increasing age. Moreover, adults were affected by visual information more than children. We discuss whether these differences in developmental patterns are due to differential integration processes for information indicative of emotions and phonemes, as well as possible cultural / linguistic reasons for these differences.